Online Annex – Economic Challenges of Lagging Regions: Annex II – Econometric Analysis and Supplemental Tables - Stefan Jestl; Roman Römisch (The Vienna Institute for International Economic Studies (wiiw), 2017)
This report is an annex to wiiw Research Report 423, 'Economic Challenges of Lagging Regions III Recent Investment Trends and Needs'. Based on spatial econometric methods, it provides estimates and simulations of the investment effects on economic development in the EU lagging regions. It also provides additional data related to the analysis in wiiw Research Report 423.
Additional information: The full report is available here: http://hdl.handle.net/10419/204195
Keywords: C15; C31; C80; R11; Y10; 330; regional economic development; EU; lagging regions; regional policy; economic challenges; investment; foreign direct investment; structural funds